Physical activity as a remedy for "cheerful" aging which prevents from chronic diseases - Alicja Rzepka; Krzysztof Radziszewski; Kornelia Kędziora-Kornatowska; Maciej Dzierżanowski (Kazimierz Wielki University, 2016)
Purpose. According to GUS, only 3.6% of the elderly declare active leisure activities. The objective of this study was to evaluate the effect of motor function improvement program implemented in sanatorium on functional condition and functional status of patients suffered from spinal degenerative diseases. Methods. The studies were carried out once in a group of 46 patients aged above 60 in Solanki Inowrocław health resort. The assessment was made based on a questionnaire. Moreover, assessment of pain in the lumbar spine according to thee VAS was made along with evaluation of lumbar spine mobility using Zebris MLS. Results. Evaluation of patients in terms of free time spending have showed that more than half of patients spent their free time actively (57%). The intensity of pain according to the VAS, during flexion, extension, rotation in both direction and lateral flexion of the spine, was decreased at the end of therapy. Flexion, extension and rotation in the right sight increase when Zebris MLS was used before and after therapy. Rotation to the left and lateral flexion to the left were not change. Conclusion. Rehabilitation in sanatorium mobilizes physical activity of patients. It improves the physical activity by significant increase in the motion range of the spine. It exerts a significant analgesic effect.